2004
DOI: 10.1061/(asce)0733-9364(2004)130:4(598)
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Visualization of Construction Scheduling and Site Utilization

Abstract: Four-dimensional (4D) models link three-dimensional geometrical models with construction schedule data. The visual link between the schedule and construction site conditions is capable of facilitating decision making during both planning and construction stages. The emphases of these 4D developments have often been placed at the level of construction components. Practical features assisting site management are at times lacking in the following areas: generation of site usage layouts; estimation of quantities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 7 publications
0
47
0
1
Order By: Relevance
“…El principal aporte a esta área en específico es que los modelos que consideran la dimensión del riesgo pueden mostrar problemas de accesibilidad y congestión dentro de la obra durante todo el proyecto (Mourgues y Fischer, 2001), con esta información se pueden prevenir los conflictos espaciotiempo (Chau et al, 2004;Su y Cai, 2014), para de esta manera ser capaces de formalizar las muchas incertidumbres que surgen durante las siguientes fases de la planificación (Mula et al, 2006). La clasificación y cuantificación de los riesgos se hace necesaria para tener una hoja de ruta con la cual mitigar los riesgos durante el desarrollo del proyecto; con ella es posible transformar información subjetiva y variables cualitativas a otras matemáticamente operables y con ello tener un monitoreo de la seguridad durante la construcción (Ding et al, 2014; Nieto-Morote y Ruz-Vila, 2011).…”
Section: Riesgosunclassified
“…El principal aporte a esta área en específico es que los modelos que consideran la dimensión del riesgo pueden mostrar problemas de accesibilidad y congestión dentro de la obra durante todo el proyecto (Mourgues y Fischer, 2001), con esta información se pueden prevenir los conflictos espaciotiempo (Chau et al, 2004;Su y Cai, 2014), para de esta manera ser capaces de formalizar las muchas incertidumbres que surgen durante las siguientes fases de la planificación (Mula et al, 2006). La clasificación y cuantificación de los riesgos se hace necesaria para tener una hoja de ruta con la cual mitigar los riesgos durante el desarrollo del proyecto; con ella es posible transformar información subjetiva y variables cualitativas a otras matemáticamente operables y con ello tener un monitoreo de la seguridad durante la construcción (Ding et al, 2014; Nieto-Morote y Ruz-Vila, 2011).…”
Section: Riesgosunclassified
“…Time is a very unique non-material element in construction projects that can be presented in various perspectives including time-space conflicts [10] and construction schedule visualization [11]. Attempts at incorporating time as additional information to evaluate and analyse different kinds of project sequences comes in the form of 4D Computer Aided Design (CAD) [12].…”
Section: Time As 4d In Building Information Modellingmentioning
confidence: 99%
“…Due to capabilities of building information modeling (BIM) in managing object-based information, some studies have suggested the use of BIM to manage site layout objects and their properties for site layout planning (Zhang and Hu 2011; Hu and Zhang 2011; Sulankivi et al 2009;Chau et al 2004). As BIM facilitates managing the information on site space and object dynamics, it can serve as a suitable implementation platform for site layout planning models.…”
Section: Moving Objectsmentioning
confidence: 99%